MODEL PEMBELAJARAN KARAKTER DI PONDOK PASANTREN - Dr. Mardyawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2015)
Character development as one of the priority programs of national development which is implicitlyaffirmed the National Long-Term Development Plan (RPJPN) 2005-2025. Therefore, to realize it inaccordance with the national culture is certainly not solely carried out in schools and Pasantrenthrough a series of teaching and learning activities outside of school, but also through habituation(habituation) in life. This is the main basis so it is said that education is the Pondok Pasantren easierto form the character of students as learning models that do more dominant model of learningthrough habituation. Eg learning model halaqah, methods sorogan, Weton, Muhawarah,Mudzakarah, Memory, Demonstration. This model was developed at the Pondok Pasantren learningand being able to shape the character of the students. As is understood that the character is